2017
DOI: 10.7554/elife.27301
|View full text |Cite|
|
Sign up to set email alerts
|

Blockade of the LRP16-PKR-NF-κB signaling axis sensitizes colorectal carcinoma cells to DNA-damaging cytotoxic therapy

Abstract: Acquired therapeutic resistance by tumors is a substantial impediment to reducing the morbidity and mortality that are attributable to human malignancies. The mechanisms responsible for the dramatic shift between chemosensitivity and chemoresistance in colorectal carcinoma have not been defined. Here, we report that LRP16 selectively interacts and activates double-stranded RNA-dependent kinase (PKR), and also acts as scaffolds to assist the formation of a ternary complex of PKR and IKKβ, prolonging the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…For instance, MacroD1 has been shown to bind and regulate proteins such as the transcription factors ERα, AR and NF-κB ( Han et al, 2007 ; Yang et al, 2009 ; Wu et al, 2011 ). More recently, MacroD1 has been shown to bind and selectively activate, the primarily cytosolic protein ( Jeffrey et al, 1995 ), Protein Kinase R (PKR) ( Li et al, 2017 ). In this study we have shown that endogenous MacroD1 is highly enriched in and primarily localizes to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MacroD1 has been shown to bind and regulate proteins such as the transcription factors ERα, AR and NF-κB ( Han et al, 2007 ; Yang et al, 2009 ; Wu et al, 2011 ). More recently, MacroD1 has been shown to bind and selectively activate, the primarily cytosolic protein ( Jeffrey et al, 1995 ), Protein Kinase R (PKR) ( Li et al, 2017 ). In this study we have shown that endogenous MacroD1 is highly enriched in and primarily localizes to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that MacroD1 is involved in several important signaling pathways: In breast cancer-derived MCF-7 cells, MacroD1 expression is induced by estrogenic hormones in an estrogen receptor alpha (ERα)-dependent manner and subsequently acts as a cofactor for ERα and the androgen receptor (Han et al 2007;Yang et al 2009). In response to DNA double-strand breaks, MacroD1 is activated and enriched in the cytosol, which stimulates prosurvival and antiapoptotic functions of the dimeric (p65/p50) transcription factor NF-κB (Li et al 2017). MacroD1 stimulates the activity of NF-κB through the interaction with p65 and UXT, a transcription factor coregulator (Wu et al 2011(Wu et al , 2015.…”
Section: Macrod1 and Macrod2mentioning
confidence: 99%
“…This might result in cytoplasmic and nuclear localisation, similar to our observation with the N-terminally truncated mutant that no longer is mitochondrial. Alternatively, some of these nuclear interactions may result from the fusion of an N-terminal tag 31,34,58 , which can result in an inaccessible MTS leading to aberrant nuclear localisation, as seen in our live-cell imaging (Fig. 2b).…”
Section: Discussionmentioning
confidence: 93%